The influence of some solution candidate on the performance of boundary element inverse analysis in detecting rebar corrosion. (August 2019) - Fonna, S; Gunawarman; Huzni, S; Ariffin, A K
Abstract: The purpose of this research is to study the effect of some solution candidate to the performance of boundary element inverse analysis (BEIA) that utilized for detecting corrosion of reinforcing steel/rebar in concrete. BEIA was developed by combining the boundary element method (BEM) and particle swarm optimization (PSO). BEM was used to calculate the electrical potential on the whole domain of reinforced concrete. While PSO was to optimize cost function to detect the rebar corrosion in concrete. BEIA was applied by using several measured electrical potential data as a reference such as from half-cell potential measurement. Numerical simulation on reinforced concrete with single rebar show that the increase of some solution candidate would resulting in increasing the number of iterations for the solution become convergence. However, the average error from the actual solution would be smaller by increasing solution candidate number. Therefore, the number of solution candidate affect the performance of BEIA in detecting rebar corrosion in concrete.